The 30th EPIC: The Scottish Ezra Pound. (The 30th Ezra Pound International Conference “Ezra Pound and the Legacy of The Cantos”, Edinburgh, Great Britain, June 27–30, 2023) - Karina R. Ibragimova (Литература двух Америк, 2023)
The article provides an overview of the 30th international conference “Ezra Pound and the Legacy of The Cantos”. The conference was held at the University of Edinburgh (June 27–30, 2023). The conference was attended by researchers from fifteen countries, including scholars from the USA, China, Germany, France, South Korea, Great Britain, Russia. The forum was attended by over 60 delegates — teachers, scholars, writers, translators. The conference topics covered all aspects of the life and work of Ezra Pound, including not only the main theme of the conference — Pound's global epic The Cantos — but also addressed the study of the American poet’s early poetics, his last years, his opinions on science, politics, history, and the circle of his personal contacts. The main vectors of the conference were (1) Pound’s London years; (2) his Asian (Chinese and Japanese) studies; (3) the legacy of Antiquity, the Middle Ages and the Renaissance in Pound's work; (4) Pound’s image in different world cultures and literatures; (5) the methods of translation used by Pound; (6) different approaches to the analysis of The Cantos. A fruitful and heated discussion was sparked by the topic “Is there a future for Pound studies?” proposed for the roundtable discussion at the final section. One of the most important features of the conference was its focus on the study of not only Pound's poetry, but also on the poetry of contemporary authors: according to the established tradition, the closing panel of the conference was dedicated to poetry readings and subsequent discussion.